The travelling patient: A clinician's guide to the law surrounding medical tourism. (December 2014) - Sim, Nicholas Keyi
European law stipulates that all patients in the European Union (EU) have the right to seek state-funded healthcare in other EU nations as if they were being treated in their home country. This means they should not incur additional costs for their home country's healthcare system. In cases of clinical negligence, patients are unlikely to bring a successful claim against the National Health Service (NHS). They face additional challenges if they bring the foreign service provider to an English court; they would need to establish jurisdiction, the applicable law, and enforce a successful judgment. The NHS may have to bear the cost of corrective treatment which is unlikely to be fully restorative. Clinicians need to be aware of the law so that they can reach a shared decision with the patient which takes into consideration the risks to the patient and service provision within the NHS.